The Contribution of the School Committee in Improving the Quality of Islamic Religious Education - Jamilus Jamilus (Ta'dib, 2023)
This study aims to describe the contribution of the School Committee in improving the quality of Islamic religious education at MTsN Solok City. The School Committee, which should carry out its duties and functions properly is still faced with many problems so that the quality of education in general and the quality of Islamic Religious Education (PAI), especially in the madrasa, has not shown the expected results. This research is field research (field research). The approach used is a qualitative approach. Sources of data for this research include School Committees, Principals, Deputy Principals of Madrasahs, and teachers of religious subjects. Collecting data using observation techniques, questionnaires, and documentation studies. Analysis data using the inductive method. The research credibility test uses observation persistence, source triangulation, and interview triangulation results with observations. The results of this study indicate that the contribution as a supporting body such as holding regular meetings with parents/guardians of students, providing support for infrastructure, and also funds to support PAI activities. Contributions as a controlling body such as supervising the planning and implementation of PAI activities, being involved in the ratification of the PAI program, supervising the progress of students' attitudes and skills after participating in PAI activities, monitoring students who excel in PAI activities, controlling the income and expenses of PAI activities. Contributions as a liaison body such as fostering collaboration with stakeholders, disseminating PAI policies and programs, and facilitating various program policy inputs.